Functional connectivity predictors and mechanisms of cognitive behavioural therapies: A systematic review with recommendations. (April 2016) - Mason, Liam; Peters, Emmanuelle; Kumari, Veena
Objective: While there is now strong evidence that psychological therapies can alter the activity of individual brain regions, their impact on the functional integration between regions has not yet been systematically evaluated. This area is important given that brain dysconnectivity has been implicated across almost all psychiatric disorders. Accordingly, we sought to establish connectivity predictors and mechanisms of effective psychological therapies. We further establish whether connectivity changes represent normalisation of disorder pathophysiology or compensatory changes. Method: We reviewed studies examining structural and functional connectivity longitudinally as either a predictor or outcome variable of successful psychological therapies across psychiatric disorders. Results: Fifteen studies met our inclusion criteria. All but three related to cognitive behavioural therapy. Of these, five assessed resting state, nine probed affective processing and one probed cognitive processing. Twelve studies reported evidence of functional connectivity as a significant predictor or outcome of cognitive behavioural therapy, with prefronto-limbic circuitry most commonly implicated. Only six studies included healthy participants, limiting direct inferences about normalisation as opposed to compensatory changes. Anxiety disorders were overrepresented, totalling 13 of the studies reviewed. No studies examined structural connectivity or utilised analyses allowing the directionality of functional connectivity to be inferred. Conclusion: While the evidence base is still in its infancy for other therapy approaches, there was clearer evidence that functional connectivity both predicts and is altered by cognitive behavioural therapy. Connections from prefrontal cortex appear especially key, perhaps given their role in cognitive appraisal of lower order affective, motivational and cognitive processes. A number of recommendations are made for this rapidly developing literature.